Inferotemporal-frontal Disconnection: The Uncinate Fascicle and Visual Associative Learning in Monkeys. - Eacott, M; Gaffan, D (1992)
We report a series of six experiments in which we examined the behavioural effects of disconnecting the inferior temporal cortex from the prefrontal cortex in cynomolgus monkeys by sectioning the direct cortico-cortical pathway between them, the uncinate fascicle. In experiment 1, monkeys with bilateral section of the uncinate fascicle showed a marked deficit in learning visuomotor conditional problems. Experiments 2 and 3 demonstrated that this deficit was not the result of a mild motor impairment, nor of a visual discrimination impairment. However, experiment 4 showed that the impairment extended to visual - visual conditional learning. In contrast, following bilateral section of the uncinate fascicle monkeys were unimpaired at two other tasks of visual associative learning: a reward - visual associative task (experiment 5), in which the presence or absence of a food reward served as a cue to the correct choice between two visual stimuli, and a time - visual associative task (experiment 6), in which the cue to the correct choice was the length of the intertrial interval. Thus, animals with uncinate fascicle section showed no impairment in learning to choose between visual stimuli based on their differential association with food reward or other non-visual cues, but were unable to learn to choose between visual stimuli based on their differential association with another visual stimulus. They were equally unable to choose between two motor responses on the basis of the visual cue.